Mature Religiosity Scale: Validity of a New Questionnaire - De Vries-Schot, Margreet; Pieper, Joseph Z.T.; van Uden, Marinus H.F. (European Journal of Mental Health, 2012)
In order to validate a new questionnaire, the Mature Religiosity Scale (MRS), it was presented to a sample of 336 persons, of which 171 were parishioners and 165 outpatients of Christian mental health clinics. A first version of this questionnaire was designed by studying both psychiatric/psychological and theological literature. Validity and reliability were studied by including other questionnaires, among them the Spiritual Well-Being Scale (SWBS), the Duke Religion Index, the Religious/Spiritual Coping (RCOPE) and the State-Trait Anxiety Inventory (STAI). The results indicate that 16 items of the 19-item questionnaire make up one factor with good internal consistency, which is measured by Cronbach’s alpha. This factor was used as the Mature Religiosity Scale in this study. Out of correlations with other validated scales and correlations with characteristics of known groups this scale proved to have good validity. The Mature Religiosity Scale is suitable for use in both mental healthcare and pastoral care. It is designed and validated for these two groups, giving direction to professional communication about faith and meaning of life.